2006
DOI: 10.1099/vir.0.81768-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a virus-inducible non-coding RNA in mouse brain

Abstract: Japanese encephalitis virus or Rabies virus results in the activation of a gene encoding a novel, non-coding RNA (ncRNA) in the mouse central nervous system. This transcript, named virus-inducible ncRNA (VINC), is identical to a 3?18 kb transcript expressed in mouse neonate skin (GenBank accession no. AK028745) that, together with a number of unannotated cDNAs and expressed sequence tags, is grouped in the mouse unigene cluster Mm281895. VINC is expressed constitutively in early mouse embryo and several adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 20 publications
4
90
0
1
Order By: Relevance
“…that are directly or indirectly required for mRNA processing and translation. In contrast, regulatory ncRNAs are usually themselves tightly developmentally regulated (reviewed by Goodrich & Kugel, 2006;Hirsch et al, 2006;Saha et al, 2006), and they have been shown to be involved in diverse biological mechanisms, such as the control of chromosome architecture, transcriptional regulation, developmental timing of protein synthesis, and mRNA turnover, and they may also regulate alternative splicing (Ling et al, 2005; reviewed by Goodrich & Kugel, 2006;Mattick, 2003;Morey & Avner, 2004). At least one non-coding RNA gene, HAR1F in humans, shows significant evolutionary acceleration, and is associated with the unique biology of that species in terms of brain development (Pollard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…that are directly or indirectly required for mRNA processing and translation. In contrast, regulatory ncRNAs are usually themselves tightly developmentally regulated (reviewed by Goodrich & Kugel, 2006;Hirsch et al, 2006;Saha et al, 2006), and they have been shown to be involved in diverse biological mechanisms, such as the control of chromosome architecture, transcriptional regulation, developmental timing of protein synthesis, and mRNA turnover, and they may also regulate alternative splicing (Ling et al, 2005; reviewed by Goodrich & Kugel, 2006;Mattick, 2003;Morey & Avner, 2004). At least one non-coding RNA gene, HAR1F in humans, shows significant evolutionary acceleration, and is associated with the unique biology of that species in terms of brain development (Pollard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1), suggesting that Men e/ b transcripts are, in fact, present at a higher level in myotubes. In addition to muscle differentiation-related regulation, Men e transcripts have been reported to be up-regulated in mouse brain infected with Japanese encephalitis virus or Rabies virus (Saha et al 2006), although the biological significance of this induced expression remains to be explored.…”
Section: Dynamic Regulation Of Ncrnas During Muscle Differentiationmentioning
confidence: 99%
“…NEAT1 transcription can be significantly influenced by p53 and is often up-regulated by stresses, such as hypoxia, viral infection/products, and genotoxic agents (Saha et al 2006;Choudhry et al 2014;Imamura et al 2014;Adriaens et al 2016). Unsurprisingly, there is also a strong link between high NEAT1 expression and more aggressive forms of cancer (Chakravarty et al 2014;Chai et al 2016;Chen et al 2016;Fu et al 2016;Ma et al 2016;Sun et al 2016;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%